Filsafat Al-Fârabî Sebagai Kritik Ideologi - Burhanuddin, Nunu (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
The scientific heritage of Abu Nasr al-Farabi is known to the world of Islam around fifty years ago and hasn’t been fully explored and researched. For about a thousand year or more, al-Farabi philosophy has been forgotten and most of his works and masterpiece was let alone and remain untouched and almost vanished. This condition seeks an effort to place al-Farabi work in Islamic constellation horizon proportionally and comprehensively. This research is aimed at investigating al-Farabi philosophy as one of the creative and original Muslim philosophical work ideology critic. “Ideology critic” in this context is an indication that a system function’s properly and cover ‘a thought’ and influence the material at the thought it self. Some of al-Farabi’s thought can be interpreted as a concept related to ideology critic it carries, just the emergence at the greatest Greek works translation project in Islamic world, the tendency of al-Farabi to logic matter built by Aristoteles as well as problems in the best country.